Learning to See New Things: Using Criteria to Support Pre-service Teachers' Discernment in the Context of Teachers' Relational Work - Holmstedt, Pernilla; Jönsson, Anders; Aspelin, Jonas (Frontiers in Education, 2018)
The purpose of this study was to investigate how preservice teachers’ understanding of relational competence can be supported through the use of digital video and explicit criteria. The study is a mixed method intervention study, where preservice teachers analyzed the teacher-student relationship as depicted in a short video sequence with the support of explicit criteria. These analyses were analyzed with content analysis according to the criteria and a thematic comparison of preservice teachers’ analyses before and after the access to explicit criteria. Findings suggest that the use of explicit criteria supported preservice teachers’ discernment of significant dimensions of teacher-student relationships, so that they were able to discern and discuss aspects of the teacher-student relationship with a specific focus on teacher-student interaction and with greater detail and nuance. The study also provides some tentative evidence that modelling the use of criteria may support preservice teachers’ use of the criteria.